SUN-525 Burosumab Experience In A UK Adolescent Population - Dharmaraj, Poonam (J Endocr Soc, 2019)
Objectives X-linked hypophosphatemia (XLH) is a rare inherited form of osteomalacia characterised by low blood phosphate levels which lead to inadequate mineralization of bone:rickets leading in turn to a spectrum of skeletal abnormalities, physical impairment, weakness, and pain. Burosumab is an anti-FGF23 fully human monoclonal antibody, and the first treatment to target the underlying pathophysiology of XLH. The trials that formed the basis of regulatory approval of burosumab only included patients up to the age of 12 years old and so data are lacking on this important patient population. We report relevant biochemical data on this population for the first three months of burosumab treatment in a real-world setting. Methods An early access program (EAP) for burosumab was made available for children in the United Kingdom with XLH in 12 specialist centres. Inclusion criteria for the EAP included radiographic evidence of disease, XLH confirmed by genetic PHEX mutation, confirmed familial X-linked inheritance mutation or family history. Patients must have also had an unsatisfactory response to best available care and treatment. EAP enrolment was between January and March 2018. A total of 142 applications were received of which 135 were approved with 132 receiving treatment to date.(1) Of the 7 declined, 4 failed to meet diagnostic criteria and 3 had insufficient radiological evidence.(1) Treatment, including dose, was in accordance with the EMA marketing authorisation. Results Data are available on 41 patients who have completed the initial 12-week burosumab titration period. This includes 7 adolescents (13 years old or over) in whom results are available for the same period. The mean height and weight at week 0 was 147.79 cm (136.6-157.8 cm) and 48.23 kg respectively. The mean dose administered was 0.38 mg/kg at week 0 and 0.92 mg/kg at the end of the initial titration period at week 12. Mean serum phosphorus was 0.59 mmol/L (0.35-0.90 mmol/L) in week 0 rising to 0.92 mmol/L (0.57-1.13 mmol/L) at week 12 representing a 56% increase in serum phosphate levels. Mean serum ALP fell from 456 IU/L (288-554 IU/L) at week 0 to 328.9 IU/L (190-461 IU/L) at week 12, representing a 28% decrease in ALP. To date, no patients have discontinued treatment to date due to adverse events.(1)Conclusions Early data from treating adolescents with XLH with burosumab in a real-world UK setting demonstrate that key biochemical responses are in line with findings from the clinical study program, which included only children 12 years and younger. This provides reassurance that the improvement in key biochemical parameters is consistent across all ages within its licensed indication. Further long-term evidence is required to confirm that the biochemical response translates to the expected impact on skeletal and non-skeletal outcomes in a clinical setting. References 1. Kyowa Kirin - data on file